Capillary microfluidics for diagnostic applications: fundamentals, mechanisms, and capillarics - Khanjani, Elham; Fergola, Andrea; López Martínez, Joan Antoni; Nazarnezhad, Simin; Casals Terre, Jasmina; Marasso, Simone Luigi; Aghajanloo, Behrouz (Frontiers in Lab on a Chip Technologies, 2025)
Microfluidic systems, especially those using capillary forces, have recently attracted considerable interest due to their potential to facilitate passive fluid management in portable diagnostic devices and point-of-care settings. These systems utilize capillary forces to autonomously regulate fluid flow, eliminating the requirement for external power and providing a more straightforward and economical option compared to active microfluidic systems. This review examines the fundamental concepts of capillary-driven microfluidics, emphasizing significant progress in the design of capillary pumps and valves, as well as the influence of surface tension, wettability, and the geometrical configurations of microchannels on the enhancement of fluid dynamics. Furthermore, the review explores other configurations, such as porous and solid substrates, to illustrate their potential for healthcare and biochemical applications. Moreover, the challenges related to managing flow rates and enhancing the reproducibility of devices are addressed, alongside recent innovations designed to overcome these challenges. Capillary systems offer an effective and reliable foundation for developing miniaturized diagnostic instruments, which hold significant potential across various domains, including biological research and environmental monitoring.